Budd-Chiari syndrome from pleomorphic sarcoma compressing the inferior vena cava: A case report - Brandon Camp, BS; Clifford N. Danza, BS; Cameron Fateri, MD; Shawn Sun, MD; Michael Phillipi, BA; Roozbeh Houshyar, MD (Radiology Case Reports)
Budd-Chiari syndrome is a rare condition characterized by obstruction of the hepatic veins or inferior vena cava, leading to portal hypertension and liver dysfunction. While common etiologies include thrombosis or malignancy, we present, to our knowledge, the first reported case in the English-language literature of Budd-Chiari syndrome secondary to metastatic undifferentiated pleomorphic sarcoma. A 52-year-old male with an extensive history of metastatic undifferentiated pleomorphic sarcoma presented with a 10-day history of vomiting and abdominal pain. A contrast-enhanced computed tomography scan of the abdomen revealed a large mediastinal mass representing likely further metastasis compressing the suprahepatic inferior vena cava, resulting in severe congestive hepatopathy consistent with Budd-Chiari syndrome. While hepatocellular carcinoma, renal cell carcinoma, leiomyosarcoma, and other malignancies have been linked to Budd-Chiari syndrome, this report highlights a novel cause. In cases of Budd-Chiari syndrome secondary to malignancy, vessel obstruction may result from compression, infiltration, or bland thrombus formation.